PENINGKATAN KAPASITAS KELUARGA PASIEN DALAM MENGELOLA NYERI MELALUI TEKNIK RELAKSASI NAPAS DALAM DI RUANG ANGGREK RSUD SUMEDANG - Bambang Aditya Nugraha, Bambang Aditya Nugraha; Sulastini, Sulastini; Sandra Pebrianti, Sandra Pebrianti (LP4M STIKes Karsa Husada Garut, 2023)
Pain is one of the problems encountered in patients with surgical cases. If not handled properly, pain will cause discomfort, sleep disturbances, and a decrease in quality of life. Families are expected to be able to teach deep breathing relaxation techniques to patients in managing pain at home with mild to moderate intensity. To achieve this capacity, community service activities are held which aim to improve the family's ability to perform deep breathing relaxation techniques. The activity took the form of a short training in the orchid room at Sumedang Hospital, which was attended by 16 people. The pre and post test results showed an increase in family capacity in performing deep breathing relaxation techniques (p=0.01). Thus, the activities carried out are useful for increasing family capacity in managing pain. It is hoped that this activity will continue to be carried out in other similar cases with the aim of relieving pain and improving quality of life.